Neglected zoonotic helminthiases in wild canids: new insights from South America - Uribe, Manuel; Brabec, Jan; Chaparro-Gutiérrez, Jenny J.; Hermosilla, Carlos (Frontiers in Veterinary Science, 2023)
The global threat of neglected tropical diseases (NTDs) constitutes a public health issue in underdeveloped countries. Zoonotic helminthiases are the most common human NTD agents in developing countries in sub-Saharan Africa, Asia, and the Americas, causing a global burden of disease that exceeds that of more recognized infectious diseases such as malaria and tuberculosis. Wild canids are well-known mammals that act as natural reservoirs of zoonotic-relevant helminthiasis worldwide, thus playing a pivotal role in their epidemiology and transmission to humans. Here we evaluate the occurrence of zoonotic gastrointestinal helminths in two Neotropical wild canid species from the Amazonian and Andean regions of Colombia, i.e., the bush dog (Speothos venaticus) and the crab-eating fox (Cerdocyon thous). We recovered tapeworm proglottids from bush dog fecal samples and identified them molecularly as the canine-specific lineage of Dipylidium caninum by using cytochrome c oxidase subunit I (cox1) gene sequences. Moreover, examination of a crab-eating fox during necropsy revealed the presence of non-embryonated eggs of the neglected nematode Lagochilascaris cf. minor, in addition to eggs and gravid proglottids of the cestode Spirometra mansoni. These findings represent the first report of zoonotic-relevant cestodes, i.e., D. caninum (“canine genotype”), S. mansoni, and the nematode L. cf. minor, in bush dogs and crab-eating foxes as final hosts. The occurrence of these zoonotic helminthiases in wild canid species calls for regular monitoring programs to better understand the epidemiology and transmission routes of neglected dipylidiasis, lagochilascariosis, and sparganosis in South America.